Effect of Acid Treatment on Interfacial and Foam Properties of Soy Proteins - Abirached, Cecilia (2015)
The goal of the present work was to study the effects of acid treatment on the foaming properties of a soybean protein isolate (SPI) and its fractions, glycinin (11S) and β-conglycinin (7S). The structural characteristics, interfacial properties, foaming capacity and stability of the treated proteins were studied. Results from surface hydrophobicity and differential scanning calorimetry (DSC) showed that the acid treatment caused the complete denaturation of 11S and a partial denaturation of 7S. This protein unfolding affected their interfacial properties, which led to an improvement in the foaming properties of both protein fractions and isolate. Treated 7S showed the best behavior in the rearrangement process, probably due to its smaller size and its modified structural characteristics. All treated proteins showed stronger interfacial films. The foams of treated proteins were destabilized mostly due to gravitational drainage rather than Ostwald ripening.